Question
upstudy study bank question image url

Solve the system of equations by any method. \[ \begin{array}{r}-2 x+5 y=-21 \\ 7 x+2 y=15\end{array} \] Enter the exact answer as an ordered pair, ( \( x, y \) ). If there is no solution, enter NS. If there is an infinite number of solutions, enter the general solut an ordered pair in terms of \( x \). Include a multiplication sign between symbols. For example, \( a * x \). I ?

Ask by Watson Weston. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( (3, -3) \)

Solution

Solve the system of equations \( -2x+5y=-21;7x+2y=15 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}-2x+5y=-21\\7x+2y=15\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{21+5y}{2}\\7x+2y=15\end{array}\right.\) - step2: Substitute the value of \(x:\) \(7\times \frac{21+5y}{2}+2y=15\) - step3: Simplify: \(\frac{7\left(21+5y\right)}{2}+2y=15\) - step4: Multiply both sides of the equation by LCD: \(\left(\frac{7\left(21+5y\right)}{2}+2y\right)\times 2=15\times 2\) - step5: Simplify the equation: \(147+39y=30\) - step6: Move the constant to the right side: \(39y=30-147\) - step7: Subtract the numbers: \(39y=-117\) - step8: Divide both sides: \(\frac{39y}{39}=\frac{-117}{39}\) - step9: Divide the numbers: \(y=-3\) - step10: Substitute the value of \(y:\) \(x=\frac{21+5\left(-3\right)}{2}\) - step11: Calculate: \(x=3\) - step12: Calculate: \(\left\{ \begin{array}{l}x=3\\y=-3\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=3\\y=-3\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(3,-3\right)\) The solution to the system of equations is \( (x, y) = (3, -3) \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the system of equations \[ \begin{array}{r} -2x + 5y = -21 \\ 7x + 2y = 15 \end{array} \] we can use the substitution or elimination method. Let's use elimination here. First, let's multiply the first equation by 7 to eliminate \( x \): \[ -14x + 35y = -147 \quad (1) \] Now, we multiply the second equation by 2: \[ 14x + 4y = 30 \quad (2) \] Now, we can add equations (1) and (2): \[ (-14x + 35y) + (14x + 4y) = -147 + 30 \] \[ 39y = -117 \] \[ y = -3 \] Now that we have \( y \), we can substitute it back into one of the original equations to find \( x \). Using the first equation: \[ -2x + 5(-3) = -21 \] \[ -2x - 15 = -21 \] \[ -2x = -6 \] \[ x = 3 \] Thus, the solution to the system of equations is the ordered pair \( (3, -3) \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy